2023
DOI: 10.1504/ijegn.2023.135297
|View full text |Cite
|
Sign up to set email alerts
|

A sectoral approach to the energy consumption - economic growth nexus for select Asian countries

Karen Fernandes

Abstract: Adequate attention has not been paid to understanding the relationship between energy consumption and economic growth at a sectoral level. This study attempts to understand and analyse the relationship between sectoral energy consumption and economic growth for China, India, Indonesia, Malaysia, the Philippines and Thailand by employing techniques such as ARDL bound testing approach to cointegration and Toda Yamamoto causality test. Results suggests that for China and India, industrial energy consumption is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Saidi, Montasser and Doytch (2022) examined the relationship between foreign direct investment, electricity consumption and financial development by using GDP, foreign direct investment and electricity consumption data of GCC countries between 1990-2019 and found that there is bidirectional causality between foreign direct investment and financial development, as well as unidirectional causality from electricity consumption to foreign direct investment and from financial development to electricity consumption. Shameem P, Villanthenkodath and Chittedi (2022) Fernandes (2023) examined the relationship between sectoral energy consumption and economic growth using energy consumption data of industrial, residential, service and agricultural sectors of China, India, Indonesia, Malaysia, the Philippines and Thailand between 1990-2018 and found that industrial energy consumption is cointegrated with economic growth for China and India, agricultural energy consumption and economic growth are cointegrated for Indonesia and Thailand, the variables are cointegrated in the service sector for the Philippines, agricultural growth causes energy consumption and agricultural energy consumption causes growth in Indonesia and Thailand. Fernandes also found that industrial growth leads to energy use in India and the Philippines while the opposite is the case in China, economic growth in the service sector leads to energy use in the Philippines while the opposite is the case in Malaysia.…”
Section: Literaturementioning
confidence: 99%
“…Saidi, Montasser and Doytch (2022) examined the relationship between foreign direct investment, electricity consumption and financial development by using GDP, foreign direct investment and electricity consumption data of GCC countries between 1990-2019 and found that there is bidirectional causality between foreign direct investment and financial development, as well as unidirectional causality from electricity consumption to foreign direct investment and from financial development to electricity consumption. Shameem P, Villanthenkodath and Chittedi (2022) Fernandes (2023) examined the relationship between sectoral energy consumption and economic growth using energy consumption data of industrial, residential, service and agricultural sectors of China, India, Indonesia, Malaysia, the Philippines and Thailand between 1990-2018 and found that industrial energy consumption is cointegrated with economic growth for China and India, agricultural energy consumption and economic growth are cointegrated for Indonesia and Thailand, the variables are cointegrated in the service sector for the Philippines, agricultural growth causes energy consumption and agricultural energy consumption causes growth in Indonesia and Thailand. Fernandes also found that industrial growth leads to energy use in India and the Philippines while the opposite is the case in China, economic growth in the service sector leads to energy use in the Philippines while the opposite is the case in Malaysia.…”
Section: Literaturementioning
confidence: 99%